Hindu-Buddhist Architecture in Southeast Asia - Chihara, Daigoro, (Asian Studies - Book Archive pre-2000., 1996)
Hinduism and Buddhism have in Southeast Asia prompted impressive architecture, including Angkor Vat and the Borubodur, with a lasting influence on the architecture of the area. This book is the first stylistic history of Hindu-Buddhist architecture in the area from the beginning until today. The contrasts and similarities described between the religious structures of the different countries shed light on the religious history of the area.